Impact of Talent Management, Job Satisfaction, and Commitment on Employee Retention - Indrati, Indrati; Ardi, Ardi; Berlianto, Margaretha Pink (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aimed to examine the effects of Recruitment & Selection, Teamwork & Management Support, Performance & Career Management, and Salary & Compensation on employees' Intention to Stay, with Job Satisfaction and Employee Commitment as mediating variables. Methodology/approach: This study employs a cross-sectional survey method. This strategy was chosen for its effectiveness because it enables the researcher to directly observe participants and gain insights into their characteristics within the workplace. Results/findings: The results show that Recruitment & Selection, Teamwork & Management Support, Performance & Career Management, and Salary & Compensation positively affect Job Satisfaction and Employee Commitment, which in turn enhance the Intention to Stay. Job Satisfaction and Employee Commitment also act as mediators in these relationships. Conclusion: All components of Ability Management positively influence Job Satisfaction and Employee Commitment, which in turn increase the Intention to Stay. The strongest relationship was between Employee Commitment and Intention to Stay, while the weakest was from Recruitment & Placement to Job Satisfaction. These findings emphasize the importance of employee satisfaction and commitment in talent retention. Limitations: This research included only 62 employees from PT XYZ, which might not accurately reflect the complete employee base of the organization or the broader manufacturing industry. Consequently, the results should not be universally applied to other companies with varying attributes. Contribution: This study combines key talent management factors and examines their impact on intention to stay through job satisfaction and employee commitment, offering deeper insights than previous research focusing on fewer aspects.